Baghdad between Prosperity and Decline: A Case Study - Dr. Kafait Ullah Hamdani; Dr. Hafiz Haris Saleem (Al Manhal Research Journal, 2024)
Baghdad, the capital city of Iraq, has a rich and tumultuous history marked by periods of prosperity and decline. This research article aims to conduct a comprehensive analysis of the factors contributing to Baghdad's prosperity and the challenges leading to its decline, utilizing a multidisciplinary approach that incorporates historical, political, socioeconomic, and environmental perspectives. By examining the historical trajectory of Baghdad and its contemporary realities, this study seeks to offer insights into the complex dynamics shaping the city's development and resilience in the face of adversity. This research article also aims to explore the multifaceted factors that have contributed to the prosperity of Baghdad throughout its history. By examining historical records, scholarly literature, and empirical evidence, this study provides insights into the geopolitical, cultural, and economic factors that have propelled Baghdad to prominence as a center of commerce, learning, and innovation.